Chromium(VI) bioreduction behavior and microbial revolution by phosphorus minerals in continuous flow experiment. (November 2020) - Ma, Linlin; Chen, Nan; Feng, Chuanping
Graphical abstract: Highlights: Sustainability of phosphorus minerals was verified by sequential batch experiments. Superb behavior in continuous flow was showed in system with phosphorus minerals. HRT acted more impacts than influent Cr(VI) on reactor behavior and microbial. The operating performance and microbial community along the reactor were analyzed. Abstract: Chromium (Cr) contamination in groundwater is a serious threat to both the environment and public health, due to its high toxicity and extensive industrial application. Based on previous studies on the enhancement of Cr(VI) bioreduction by phosphorus minerals, it is of great significance to assess its practical application potential. Towards this aim, Cr(VI) bioreduction guided by phosphorus minerals under continuous flow condition was conducted with the variation of initial concentration and HRT, where it was conservatively estimated that 5 g of phosphorus minerals can satisfy the needs of normal operation of a maximum of 200 cm 3 bioreactor at a chromium load of 40 mg/(L·d), and further analysis was performed for operating characteristics and microbial community along the route and the reactor. The results of this study provide new insights and empirical support for the in-situ bioremediation reinforcement of Cr(VI)-contaminated groundwater.